Breast Organ-Specific Surgical Practice: Perspectives of Indian Surgeons (Journal of Analytical Oncology, 2025)
Objectives: Cancer care is changing rapidly, with many countries embracing organ-specific specialization to offer more focused and effective treatment. In India, however, most surgeons continue to practice in a more generalized way, and we still do not fully understand how they feel about shifting toward subspecialized care. This question becomes especially important in breast cancer—the most common cancer among Indian women—where dedicated expertise can make a real difference in early detection, treatment quality, and patient survival. This study aims to explore how Indian surgeons view breast organ-specific practice, their willingness to adopt it, and the challenges they foresee.Methods: Cross sectional study conducted in July 2024 in 100 surgeons of India using a self-administered google form questionnaire. Responses were evaluated and assessed.Results: Out of 100 responses, 45% were from private/corporate setting, 39% from government institutes. 30.6% were from west, 27.6% from east, 22.4% from south and 19.4% from north zone. 55% were from surgical oncology, 36.4% were from general surgery. As per the study, breast (31%) and gastro-intestinal surgery (29%) were the subspeciality of choice. 47.5% agreed that they would be interested in breast specific surgery practice if proper training was available. 30.9% considered this to be less stressful with fewer complications. Majority (48%) thought that lack of patient awareness about breast cancer specific surgeon was the biggest disadvantage of organ specific practice. 22% considered it to be technically undemanding. 51% and 27.1% suggested that a dedicated and recognized training is required and organ specific practices are required at hospitals/institutions respectively. Notably, female surgeons were more likely to choose breast surgery compared to males (50% vs. 20%), a difference that was statistically significant (p = 0.015; 95% Confidence Interval (CI): 1.50–12.25)Conclusion: Breast organ specific oncosurgery practice is still uncommon in India. More dedicated training programs are required along with adequate employment opportunities to fill the lacunae in promoting the same.